THE EFFECT OF MOTIVATION AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE PRODUCTIVITY AT PT. AMAN SEJAHTERA GLOBAL - Mifta, Mifta Farid Salam; Fakhruddin Kurnia M; Mariam Makmur (Universitas Ichsan Sidenreng Rappang, 2023)
This study aims to determine whether motivation and work experience affect the productivity of employee performance at PT. Aman Sejahtera Global This data collection uses a quantitative approach and primary data sources in the form of questionnaires distributed to the entire study population using a purposive sampling method. The population is all employees of PT. Aman Sejahtera Global, while the sample is 30 people, has also been tested regression and correlation, analysis methods and hypothesis testing. The data analysis method uses multiple regression techniques. The results showed that there was no partial positive and significant effect of motivation on employee performance productivity. However, there is a positive and significant effect of work experience on employee performance productivity. This shows that motivation has no effect on employee performance productivity but work experience has a significant positive effect on employee performance productivity at PT. Aman Sejahtera Global